Great expectations : The computerization of research and educational literature in Swedish university libraries 1960-1980 - Olsson, Lena (2006)
Searching for information in databases or on the world wide web to enhance our knowledge has become an everyday task. The internet is a major source of information for education. When we want to make new material available in digital form, we examine how contents can be made searchable by the creation and attachment of metadata. We now have expectations that most educational material, literature and research will be described and to a great extent also readable as full-text in digital form. For the benefit of future university research and teaching the digital global university library is a prevailing image. The work of organizing and representing information with metadata and make it searchable and usable for education and research started already in the 1960’s. A vision of the global library was presented during the same period originating from the Library of Congress in Washington DC.(Library of Congress,1963)1 Some of the expectations, discussions and choices which took place during this period can be recognized as having meaning for processes 20-40 years later.